Luminescence properties of Ce3+doped gadolinium-calcium-silicaborate glass scintillator - J. M. Park (2018)
© 2016 Elsevier Ltd In this work, the Ce3+doped gadolinium-calcium-silicaborate glass scintillators of the composition ratio 25Gd2O3:10CaO:10SiO2:(55−x)B2O3:xCeF3, have been fabricated by using the melt-quenching technique. The doping concentration of the Ce3+was varied from 0.05 mol% to 2.5 mol%. The 4f-5d transition of the Ce3+allowed scintillation with a fast decay time. The absorption spectrum, X-ray induced emission spectrum, photo luminescence spectrum, laser luminescence spectrum and decay time of the scintillators were measured for studying the luminescence properties. From the X-ray induced emission spectrum result, we checked the trend between doping concentration and light yield. The laser induced luminescence spectrum was measured while changing the temperature from 300 K to 10 K. We also measured the decay time by using the laser excitation of the 0.15 mol% Ce3+doped glass scintillator.